Bird Diversity in The Coastal Area of Sekotong, West Lombok - Larasati, Sri Aprilia Nur; Alawiyah, Rita; Syukur, Abdul (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Birds are wild animals that have a wide distribution, making birds one of the wild animals in the world with potential natural resources in Indonesia. This lesson aims to determine the bird diversity index in the Sekotong Tengah Coastal Area. The research was conducted in March-May 2024 in the Central Sekotong Coastal Area. The method used in this research is the exploration method by following the paths at the three observation locations. The research results showed that there were 23 families with a diversity index value of 3.986 in the Central Sekotong Coastal Area. Bird diversity in the central Sekotong Coastal Area is relatively high. Further research is recommended to determine the distribution of birds in the Sekotong Tengah Coastal Area to become a Birdwatching area.